(untitled) - Afyouni, Hassan A. (Boston, 2006)
This groundbreaking approach to database security will prepare students for business applications in a non-database specific environment.
Keywords: Computer security,Database security,Bảo mật máy tính,Bảo mật cơ sở dữ liệu